Erythromycin induces supranormal gall bladder contraction in diabetic autonomic neuropathy. Issue 8 (August 1993) - Catnach, S M; Ballinger, A B; Stevens, M; Fairclough, P D; Trembath, R C; Drury, P L; Watkins, P J
Abstract : Gall bladder motor function is impaired in some patients with diabetes. It has been suggested that the abnormalities of gall bladder motility are confined to those patients with autonomic neuropathy. Erythromycin, a motilin receptor agonist, causes gall bladder contraction in both normal subjects and patients with gall stones with impaired gall bladder emptying. The effect of erythromycin on gall bladder motility in seven patients with diabetes with an autonomic neuropathy, six patients with diabetes without autonomic neuropathy, and 17 normal subjects was studied using ultrasound. There was no significant difference in gall bladder fasting volume between the three groups, but the patients with diabetes with autonomic neuropathy had impaired postprandial gall bladder emptying compared with normal subjects (percentage emptied (SEM) 40 (10.3)% v 64 (2.8)%, p < 0.01) and those with autonomic neuropathy (48 (7.7)%, NS). Erythromycin produced a dramatic reduction in gall bladder fasting volume in patients with diabetes with an autonomic neuropathy, compared with either normal subjects or patients with diabetes without autonomic neuropathy (percentage reduction 62 (4.6)% in patients with autonomic neuropathy, v 37 (17.6)% in those without autonomic neuropathy, and 26 (7.3)% in the normal subjects, (p < 0.02) and returned gall bladder emptying to normal in all patients with impaired emptying. The pronounced effect of erythromycin in diabetic autonomic neuropathy suggests denervation supersensitivity and that the action of erythromycin on the gall bladder is neurally modulated.